Ethnomedicinal Plants of Deoband Tehsil of Saharanpur District, Uttar Pradesh, India - Ahamed, Nafeesh; Gupta, A. K.; , Neetu (Indian Forester, 2010)
The present paper describes ethnomedicinal plant of Deoband tehsil of Saharanpur district, Uttar Pradesh. An ethnobotanical survey was conducted in villages of study area, during 2005-2006.74 plant species under 69 genera belonging to 42 families were found of ethnomedicinal value. The plant species are enumerated in alphabetical order with families and local names, followed by their ethnomedicinal uses.